Review article about modified nucleosides (Pro-Tide) as potential anti-HCV Therapeutics - Elsharif, N.; Dakhil, O. (Libyan Journal of Science &Technology, 2022)
Hepatitis C virus is among the most common causes of cirrhosis and chronic liver disease worldwide. As a result, many researchers are interested in designing and synthesis of a clinical treatment for hepatitis C virus. Nucleoside monophosphates and monophosphonates play an important role for treatments of incurable diseases such as hepatitis. For example, 2'-Cmethyladenosine and 2'-C-methyl guanosine have shown activities against HCV in the replicon assay as well as against several members of the flavivirus family. However, their development as drug molecules has been hindered by the inherent poor drug-like properties of the monophosphate and monophosphonate groups. The monophosphate and monophosphonate groups have low bioavailability due to the inefficient cellular uptake, poor in vivo stability and poor intracellular metabolism, the latter drawback being most relevant to monophosphates than monophosphonates. These limitations can be addressed by using portide strategy, which able to help the nucleoside monophosphate delivered inside the cell. In this review, we discuss the different keys monophosphate and monophosphonate nucleoside prodrugs that entered clinical development. In addition, the role of the protide technology that highlighted the success in the discovery of nucleoside therapeutics.